Thermal, hardness, and tribological assessment of PEEK/CoCr composites - Bakytzhan Sariyev; Andas Amrin; Aiat Mergenbay; H. Jeevan Rao; Aigerim Khabdulayeva; Christos Spitas; Boris Golman (Scientific Reports)
Abstract Poly(ether-ether-ketone) (PEEK) is a high-performance thermoplastic with excellent mechanical strength, thermal stability, and chemical resistance, making it attractive for applications like biomedical implants and prostheses. However, neat PEEK suffers from a high friction coefficient and pronounced wear in sliding contacts. In this work, composites of PEEK with Cobalt-Chromium (CoCr) alloy powder were fabricated by centrifugal powder compaction and vacuum sintering. Four composite compositions, with weight percentages of 10%, 20%, 30%, and 40% of CoCr, were produced. Scanning electron microscopy analysis confirmed uniform dispersion of CoCr particles within the PEEK matrix. Differential scanning calorimetry and thermogravimetric analysis showed that CoCr addition did not significantly alter PEEK’s melting temperature or thermal stability. Microhardness increased with filler loading, with the 40% CoCr composite achieving a 40% hardness improvement over neat PEEK. Ball-on-disk tests against steel revealed that all composites exhibited significantly reduced wear loss by 84% compared to neat PEEK, while maintaining a friction coefficient typical for PEEK-steel contacts. Overall, the PEEK/CoCr composites demonstrate enhanced hardness and wear resistance while retaining PEEK’s favorable thermal properties, suggesting their potential for applications requiring better tribological performance than unfilled PEEK.